PENGGUNAAN MEDIA SOSIAL SEBAGAI MEDIA PROMOSI DI SULTAN PIZZERIA THE SULTAN HOTEL & RESIDEN HOTEL JAKARTA - Yuliana Dwi Marwa; Sulih Wahyudiono (LPPM and Travel Operation Department Universitas Asa Indonesia, 2023)
Abstract Yuliana Dwi Marwa1, Sulih Wahyudiono, S.E., M.M.2 1Mahasiswa program studi, Akademi Pariwisata Indonesia Jakarta 2Dosen program studi, Akademi Pariwisata Indonesia Jakarta 1yulianadwi119@gmail.com, 2sulihwahyudiono@gmail.com The development of social media is currently very fast, it cannot be denied that social media is used for media promotion. The information people are looking for can be easily searched on social media without the need to go anywhere. One of the social media used by The Sultan Hotel & Residence Jakarta as promotional media for Sultan Pizzeria is Instagram, Facebook, and Twitter. By utilizing the available features, marketing communication can maximize the promotion of Sultan Pizzeria. This study aims to determine how the use of social media as a promotional media and which social media is effectively used for promotional media. This research uses a descriptive qualitative approach. The data used in this research are observation, literature study, and interviews. The result of this research is that marketing communication has not utilized the ads feature in all social media and based on the discussion, the effective social media used for the promotion media of Sultan Pizzeria are Instagram and Facebook.